O ensino de astronomia do sistema solar: uma abordagem na educação básica - Moreira, Tamiles Ferreira (2021)
Astronomy provides the construction of an integrated and contextualized knowledge. The present work aimed to propose to the school environment, a material with a set of activities involving the field of Astronomy, focusing on the Solar System, addressing its origin, formation, characteristics, concepts, and laws involving the present Physics, enabling active participation of teachers and students of basic education in this teaching and learning process. To reach the objectives of this work, a Qualitative and Quantitative methodology was used, in partnership with physics teachers, by reading the material produced and collecting data through a questionnaire. The educational product, linked to this dissertation, consists of an accessible didactic material, consisting of a booklet for the Teaching of Astronomy of the Solar System, to work on concepts involving the Solar System, as well as interdisciplinary suggestions for games, movies, experiments focused on Astronomy. In this way, helping in the transposition of contents aimed at the Solar System and other concepts within Astronomy that end up being worked on in a superficial or wrong way in the classroom.